Knowledge and Use of Social Media by Reference and User Services Librarians in Public and Private Universities in Ghana - Ahenkorah-Marfo, M. (University of Ghana, 2015)
Trends in global information communication have necessitated that academic libraries, whether public or private, resort to the employment of web 2.0 technologies such as Facebook, Twitter, Blogs, Wikis, RSS feeds, YouTube, etc. in their services. Indeed the knowledge and use of such platforms has become critical for the survival of academic libraries globally. For this reason, this research focused on investigating the knowledge and use of social media by reference and user services librarians. The main objectives were to determine the level of knowledge, extent of use, the major social media platforms used, as well as the perceptions librarians held about employment of social media in reference and user services. A mixed methods research approach employing Likert type questionnaire and interviews was used in soliciting the views of 105 librarians from UG, KNUST, UCC, AUC, VVU and GTUC on their knowledge and use of social media. The findings of the study indicate that majority of the librarians were knowledgeable and used social media for both personal and work-related purposes. They, however, lacked the skill needed to use the array of social media platforms available to make a difference in service delivery. As a result, though librarians had a very good perception of social media, they still found the traditional mode of service delivery more comfortable. Some of the challenges that bedeviled the practice of social media were lack of interest and skill on the part of librarians, low bandwidth and poor internet connectivity, and more importantly lack of policy to guide social media application in libraries. The study therefore, recommended re-training and re-orientation of librarians in the use of social media by e-resources and reference departments, sensitization workshops by GLA/CARLIGH to whip up interest in librarians to use social media, and adoption of policy document to guide the practice of social media in libraries.
Thesis (MPhil) - University of Ghana, 2015
Keywords: Social Media; Knowledge; Ghana; tertiary institutions; Public and Private Universities; Reference and User Services; academic Libraries; Librarians; web 2.0 technologies